Isolation of Chitinolytic Bacteria as Biocontrol Agent for Pathogenic Fungi on Cocoa Fruit in Sumbermanjing District, Malang - Sulistyantini, Cahyaning; Mustafa, Irfan; Jatmiko , Yoga Dwi (The Journal of Experimental Life Science, 2023)
The productivity of cocoa plants in Sumbermanjing District is lower than in other parts of Malang Regency. Diseases like pathogenic fungi are to blame for the low output of cocoa plants. This research aimed to find chitinolytic bacteria that were superior at degrading chitin and limiting the growth of pathogenic fungi. These bacteria were isolated from cocoa garden soil and shrimp shell dumps. The bacteria from soil samples taken from the shrimp shell dump in Ujungpangkah District and the cocoa gardens in Sumbermanjing District were cultivated on an agar medium supplemented with colloidal chitin. The pathogenic fungi were discovered from decaying cocoa pods from Sumbermanjing District cocoa plantations. An antagonist test was used to gauge the inhibitory power, and a semi-quantitative test was used to measure the chitinolytic index. The similarity of 16S rDNA sequences allowed for the identification of superior bacterial isolates. The T2S1 isolates of chitinolytic bacteria had the highest levels of pathogenic fungi inhibition (25.14%, 20.85%, and 25.24%). With a 16S rDNA sequence similarity of 99.77%, Bacillus subtilis C10 was identified as the bacterium T2S1. Keywords: Bacillus subtilis, Pathogenetic fungi, Cocoa, Chitinase, 16s-rDNA.